Coordination Behavior of N2o Donor Ligand with Some Metalsions - Al-khazraji, Ali M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Tridentate Schiff base ligand L2 and its complexes with nickel(II), cobalt (II), copper (II), manganese (II) and mercury (II) ions have been synthesized by the condensation of 4Aminoantipyrine, Benzoin, then the ligand (L1) and 3-amino benzoic acid. The ligand and its complexes were described by 1H-&13C-NMR, UV-visible, FT-IR, (only ligand), molar conductance elemental, analysis and magnetic susceptibility, calculations. It has been set that the ligand acts as (N, N, O) neutral tridentate forming chelates with stoichimetry (metal: ligand) (1:1). all metal complexes is suggested Octahedral configuration. Most of the prepared compounds show antibacterial activity to (Staphylococcus aureus),(Escherichia coli), (Bacillussubtilis) and (Pseudomonas aeroginosa).